Making APA Style Great Again! : Insights into Teaching and Learning APA Style - Peden, Blaine F.; Miller, Caitlin (My University, 2017)
There are many aspects of APA style to learn. We focus on the prominent feature of APA citations and references (Madigan, Johnson, & Linton, 1995). Landrum (2013) and other studies confirm it is difficult to teach/learn APA style with the present teaching methods (i.e., “how”). This poster introduces motive to cite (i.e. “why”) research as a possible remedy to the struggles of teaching/learning with the current methods (i.e. “how”).
Color poster with text and flow charts.
Keywords: Teaching methods; Written communication; APA style; Posters